2007
DOI: 10.1007/s00330-007-0741-8
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced MR imaging of the brain using T1-weighted FLAIR with BLADE compared with a conventional spin-echo sequence

Abstract: The BLADE and PROPELLER (periodically rotated overlapping parallel lines with enhanced reconstruction) techniques have been proposed to reduce the effect of head motion. Preliminary results have shown that BLADE also reduces pulsation artifacts from venous sinuses. The purpose of this study was to compare T1-weighted FLAIR acquired with BLADE (T1W-FLAIR BLADE) and T1-weighted spin-echo (T1W-SE) for the detection of contrast enhancement in a phantom and in patients with suspected brain lesions and to compare th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 9 publications
0
31
0
1
Order By: Relevance
“…BLADE has , c) shows that the node has an irregular border and that there is soft tissue infiltration of the muscle previously shown improvement in image quality by reducing patient motion artifacts [38] and pulsation artifacts related to vascular flow [39,40] and bowel peristalsis [41,42]. Although the study found that pulsation artifacts were reduced and upper thoracic structures were thereby better delineated, the TSE T1 technique showed better contrast between lymph nodes and fat.…”
Section: Rapid Mri Techniques For Detecting Nodal Diseasementioning
confidence: 86%
“…BLADE has , c) shows that the node has an irregular border and that there is soft tissue infiltration of the muscle previously shown improvement in image quality by reducing patient motion artifacts [38] and pulsation artifacts related to vascular flow [39,40] and bowel peristalsis [41,42]. Although the study found that pulsation artifacts were reduced and upper thoracic structures were thereby better delineated, the TSE T1 technique showed better contrast between lymph nodes and fat.…”
Section: Rapid Mri Techniques For Detecting Nodal Diseasementioning
confidence: 86%
“…Previous clinical studies have shown that a BLADE acquisition can reduce pulsation artifacts from the transverse and sigmoid sinuses at T 2 -FLAIR imaging 6 and contrast-enhanced T 1 -FLAIR in adults. 8 The reduction of this artifact from the venous sinus was also achieved in non-contrast-enhanced T 1 -FLAIR-BLADE in children.…”
Section: Magnetic Resonance In Medical Sciencesmentioning
confidence: 91%
“…The clinical use of T 1 -FLAIR-BLADE has been reported with or without gadolinium enhancement for brain imaging in adults 6,8,9 and with gadolinium contrast for brain imaging in children. 10 However, we believe the utility of T 1 -FLAIR-BLADE as a non-contrast-enhanced T 1 -weighted sequence in pediatric patients has not been well established.…”
Section: Blade [T 1 -Flair-blade])mentioning
confidence: 99%
“…Naganawa ve ark. 'nın (13) yaptığı 27 kişilik hasta grubunda, T1A FLAİR ile T1A SE sekansı karşılaş-tırmışlar, T1A SE'nun spesifitesi %55, sensitivitesi %100, T1A FLAİR sekansın spesifitesi ve sensitivitesi %100 olarak saptamışlardır. Lezyon-zemin CNR değerleri arasında ise anlamlı fark bulamamışlardır.…”
Section: Tartişma Ve Sonuçunclassified